Post a New Question

Algebra

posted by .

factor by grouping: 3X^2 + 7X -6 ? Please walk me through this

  • Algebra -

    3x^2 + 7x-6
    (X+3)(3x-2)

  • Algebra -

    3x^2 + 7x - 6

    multiply the first and last coefficients
    3(-6) = -18
    factors of -18 that add up to 7
    +9 and -2
    (9)(-2) = -18 and 9 - 2 = 7

    so replace the middle term of 7x with -2x + 9x
    3x^2 - 2x + 9x -6
    group as
    (3x^2 - 2x) + (9x-6)
    now factor each group
    x(3x-2) + 3(3x-2)
    = (3x-2)(x+3)

  • Algebra -

    x=2/3 and x=-3

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question